Rationality and State in Plato´s The Stateman and Spinoza´s TP - Ferlini Cartín, Héctor (2025)
This work problematizes how is the relationship beetwen rationality and State in Plato´s  The Statesman and Spinoza´s Political Treatise and compares how both authors explain the existence of the State, its regimes and other aspects such as science, truth, power, method and passions.